Sunflower Cost-Return Budget in Western Kansas - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Haag, Lucas; Falk Jones, Jeanne; Holman, John (My University, 2014)
This publication projects a budget that reflects expected income and costs based on typical production practices of sunflowers in western Kansas.
MF887_2014_02
Keywords: MF887; Economics; Crops; MF